How to be incredibly rich ASAP, for small service firms: Grow or not? - Poulsen, Niklas (2010)
This paper presents a study on how small service firms can improve profitability and if growth is a solution or not. Problems discussed and solutions provided will hopefully serve well to highlight points of improvement for small service firms, especially where the owners are inexperienced in business, marketing and entrepreneurship. The study is conducted with the aim of providing realistic solutions for The Norwegian Imago Institute. In the process, eight people with great insight and experience were interviewed in Norway, Sweden and Denmark and a survey sent to 250 people with 11 respondents. The paper concludes that previous experience with employment is often necessary to succeed with employment growth. However, other forms of growth proved to have great potential. In order to become more profitable, there is no magic pill. What increases the odds of success is writing a business and liquidity plan, knowing exactly what and where you want to go, innovative thinking about marketing, PR and standardization of services. The implication for small service firms that lack experience in business, marketing and entrepreneurship is mostly a realization that they have to change their view on profitability from thinking it’s a evil phenomenon of the information age to the fact that having healthy profitability might actually improve the service and experience. It is possible to deliver a personalized, intimate and great product, and still make great profits.